RT PCR Detection and Propagation of Respiratory Syncytial Virus in Human Lung Carcinoma Cells (A549) cell line - F. Ali, Layla; G. Al-Suhail, Raghad; G. Naser, Faisal (Iraqi Journal of Science, 2023)
In this study negative result of real-time reverse transcription-QPCR (RT-PCR) assaytests of Influenza virus of nasal screetion and throat swap samples of Iraqi patientshospitalized with signs and symptoms of an upper respiratory tract infection in CentralRepublic Health Laboratory in Iraq were tested for Respiratory Syncytial Virusinfection by RT PCR .Positive samples was 4 out 0f 20 were used .Viral isolation wasdone on a monolayer of 70-80% confluent Human Lung Carcinoma Cells (A549) cellline and incubated at 33ºC for 4 days .Syncytia was observed in 3 positive samples.